Wagenscheins Pädagogik neu reflektiert Mit Martin Wagenschein Bildungserfahrungen verstehen und unterstützen - Müller, Marc; Schumann, Svantje (Gespräche zum Sachunterricht, 2022)
The importance of Martin Wagenschein (1896-1988) for scientific didactics is undisputed. His ideas have been received, developed, tested and applied to new teaching contexts for over half a century. In particular, the demand to teach "understanding" continues to inspire current didactic discourses, now also beyond the area of ​​so-called STEM education. Against the background of urgent questions about successful education, Wagenschein's ideas are examined in this volume both in the past and in the future. The "First Book" (Part 1) uses primary and secondary works to show who and what inspired Wagenschein. In a comprehensive interview section, people whose work was and is significantly influenced by Wagenschein have their say. The "Second Book" (Part 2) is based on the Wagenschein Conference held in 2021 and looks at where Wagenschein's ideas and concerns are alive as an integral part of didactic and school practice and from which points of view they are being further thought and developed.